PERANCANGAN KURSI KERJA PADA STASIUN PENGUPASAN PISANG MENGGUNAKAN METODE ANTROPOMETRI DI IKM KERIPIK PISANG CIPAKU - CIAMIS - Kurnia, Yusup; Aristriyana, Eky (J-ENSITEC, 2023)
Workstations in most SMIs (Small and Medium Industries) do not pay too much attention to ergonomic aspects which result in not achieving an ECSHE system (Effective, Comfortable, Safe, Healthy, Efficient). This study aims to determine the design of a work chair at the banana peeling station at IKM Pisang Chips, Cipaku District. The data used is worker anthropometric data as a reference for designing work chairs. A total of 30 people who are the same age as the workers at the station, between 30-50 years old, were sampled for this study. Data that have been declared uniform and sufficient are then selected using the percentile concept by choosing between the 5th percentile and the 95th percentile. The anthropometric dimensions used were shoulder height in a sitting position (D10), popliteal length (D14), popliteal height (D16), shoulder width (D17) and hip width (D19). The results of this study indicate that the dimensions D10, D14, and D16 use the 5th percentile while D17 and D19 use the 95th percentile. The design produced from this study has a chair back height of 54 cm, 42 cm seat length, 32 cm chair leg height, the width of the back of the chair is 36 cm and the width of the seat is 40 cm.